Análise dialógica do gênero artigo de opinião em livros didáticos para o ensino médio - Bezerra, Maria Isabel Fernandes (2013)
Until the late 1950s, teaching Portuguese language was synonymous of teaching the grammar of the language. Since 1980, the text became the main object of teaching Portuguese. From the 2000s, as indicated by PCNEM, teaching Portuguese is teaching reading and writing speech genres. However, adopting a discursive approach in teaching language through speech genres still raises many questions. This work's objective is to understand how the teaching and learning of discourse genre opinion article in Portuguese language textbooks for high school is, adopting as theoretical and methodological basis Dialogic Discourse Analysis. The corpus is composed by the Opinion Article chapters in three textbooks that were featured for text production in PNLD 2012: Português: contexto, interlocução e sentido, Ser protagonista and Viva português. Furthermore, we investigated the official documents that guide Portuguese language teaching. Given the overall goal of understanding how to teach Portuguese language through discourse genres in the proposed high school textbooks, the specific objectives are focused on the result of the displacement of the opinion article genre from the journalistic sphere to the textbook. This analysis seeks answers to the following questions: how opinion articles are addressed at schools? Are the proposals sufficient to form readers and writers in this genre? The focus on the study of the opinion article is justified by the consideration that reading and writing can contribute to argumentation and the consequent recognition of the other, in that it presupposes the discussion of controversial issues and understanding different points of view regarding a particular theme. The article is not the presentation of a fact, such as news, or its analysis, such as the report, but a response to what has been said about it. In the Bakhtinian perspective, the author presents a point of view on a subject and in doing so incorporates to his speech voices that have spoken about it. All of this movement focuses on the reader, since the writer opines and justifies his opinion with arguments to convince the reader that he is right